Ultraviolet/blue light-emitting diodes based on single horizontal ZnO microrod/GaN heterojunction - Du, Chia-Fong (Springer, 2014)
We report electroluminescence (EL) from single horizontal ZnO microrod (MR) and p-GaN heterojunction light-emitting diodes under forward and reverse bias. EL spectra were composed of two blue emissions centered at 431 and 490 nm under forward biases, but were dominated by a ultraviolet (UV) emission located at 380 nm from n-ZnO MR under high reverse biases. Light-output-current characteristic of the UV emission reveals that the rate of radiative recombination is faster than that of the nonradiative recombination. Highly efficient ZnO excitonic recombination at reverse bias is caused by electrons tunneling from deep-level states near the n-ZnO/p-GaN interface to the conduction band in n-ZnO.